IMPLEMENTATION OF SIKOLA AMMA BAPA TO IMPROVE POSITIVE PARENTING COMPETENCE FOR ISLAMIC ACTIVISTS - Damayanti, Eka; Rusydi Rasyid, Muhammad (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2022)
Violence against children continues to increase and needs the appropriate prevention for families who are vulnerable to get violence. This service research applied the treatment of the educational model in the form of Sikola Amma Bapa to the parents or caregivers to get positive parenting competencies. This research was conducted in Gowa Regency for six months, from March to August 2020, where 15 samples were selected with purposive sampling techniques. The data collection instrument used was a parenting competency scale, adapted from the Mindfulness in Parenting Questionnaire (MIPQ) by McCaffrey and was added by some specific parenting competency items based on the Sikola Amma Bapa module. Pre- and post-test data were evaluated using inferential analysis of paired sample t-tests. The results showed that the application of Sikola Amma Bapa became effective. The model can increase the competence of care for Islamic activists in assisting vulnerable families who get violent in the Gowa regency as proven by p = 0.000 (p 0.001). The data showed a very significant difference between the pre-test and the post-test; the average after-treatment (post-test value) is 143.6667, which is higher than the treatment (pre-test value) of 107.0067. Abstrak: Kekerasan pada anak terus mengalami peningkatan sehingga diperlukan pencegahan secara tepat yang menyasar keluarga yang rentan kekerasan. Penelitian ini bertujuan untuk menerapkan perlakuan model pendidikan dalam bentuk Sikola Amma Bapa bagi orangtua/pengasuh agar membentuk kompetensi pengasuhan positif. Penelitian dilaksanakan di Kabupaten Gowa selama enam bulan dengan melibatkan sampel sebanyak 15 orang yang dipilih dengan teknik purposive sampling. Instrumen pengumpulan data yang digunakan berupa skala kompetensi pengasuhan yang diadaptasi dari Mindfulness in Parenting Questionnaire (MIPQ) dari McCaffrey dengan menambahkan item kompetensi pengasuhan secara spesifik yang sesuai dengan modul Sikola Amma Bapa. Data dianalisis menggunakan analisis inferensial paired sample t-test dengan bantuan komputerisasi. Hasil dalam penelitian menunjukkan bahwa penerapan Sikola Amma Bapa dapat meningkatkan kompetensi pengasuhan pada aktivis Islam dalam mendampingi keluarga yang rentan kekerasan di Kabupaten Gowa. Hal itu dibuktikan dari nilai p = 0.000 (p < 0.001) menunjukkan ada perbedaan sangat signifikan nilai sebelum dan setelah perlakuan dimana rata-rata nilai setelah perlakuan sebesar 143,6667 lebih tinggi dibanding nilai sebelum perlakuan sebesar 107,0067.